2019
DOI: 10.1002/ijgo.12784
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor myofascial pain in patients with symptoms of urinary tract infection

Abstract: Objective To correlate lower urinary tract symptoms typically associated with a urinary tract infection (UTI) with physical examination findings of pelvic floor myofascial pain (PFMP). Methods This retrospective review included all new patients presenting to a urogynecology clinic between August 2 and December 19, 2016. Patients completed validated questionnaires, had a catheterized urine specimen, and underwent pelvic examination. Associations between demographics, symptoms, urine culture, and PFMP were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…A recent study found stronger pelvic muscles in athletes with UI than without UI [20]. It may be due to solid pelvic muscles that fail to relax fully and increase stress leading to increased urinary frequency and eventually UI [30]. In the past, jumping was thought to have the highest prevalence for UI since it is a significant factor for PFM weakening [1].…”
Section: Association Of Sui and Nulliparous Athletesmentioning
confidence: 99%
“…A recent study found stronger pelvic muscles in athletes with UI than without UI [20]. It may be due to solid pelvic muscles that fail to relax fully and increase stress leading to increased urinary frequency and eventually UI [30]. In the past, jumping was thought to have the highest prevalence for UI since it is a significant factor for PFM weakening [1].…”
Section: Association Of Sui and Nulliparous Athletesmentioning
confidence: 99%
“…Pelvic pain and dysuria are commonly associated with MPS [ 94 ]. In a retrospective study of 250 women presenting with symptoms of urinary tract infection, 50% were found to have pelvic MPS, but only 6% had positive urine cultures [ 95 ]. This observation suggests that irritative urinary symptoms may be associated with MPS and that, in some cases, pelvic MPS can accompany urinary tract infections.…”
Section: Methodsmentioning
confidence: 99%
“…Также пациенты могут сообщать о диспареунии, нарушениях мочеиспускания, запорах, боли в вульве, влагалище, прямой кишке, ягодицах или бедрах. При этом данные симптомы не зависят от локализации триггерной точки [18]. Большинство пациентов с МФБС мышц промежности описывают боль как самопроизвольно исчезающую, длящуюся от 30 с до нескольких часов.…”
Section: раз в день -10 дней лечебно-диагностическое введение 1 мл ра...unclassified